Memórias do combate à Coluna Paulista no oeste paranaense: a escrita de si nas pajadas de um soldado (1924-1925) - Tecchio, Caroline (2012)
This study deals with the memories of a legalistic soldier who participated in the combat against Coluna Paulista in western of Paraná, between 1924 and 1925. His military experiencesare narrated in the form of pajadas , which are typical verses from gaucho culture that commonly are presented orally. The written verses show up in the Book of Notes of another soldier, Ernesto Baptista Tecchio. This book does not mention the pajador , creating thus doubts about its intention to forge or not the authorship of the verses. Ernest served in the Army in Cruz Alta, Rio Grande do Sul, while the pajador soldier went into battle leaving Alegrete city in this same state. At some point their paths crossed and Ernesto had access to the pajadas . Considering the relations established between the memories of the pajador and Ernesto, who was guardian and partner of this memory, this study examines the written content about himself contained in the registers.In different ways, these individuals keep their opinions through narratives. Using the theory of authors who discuss memorialistic aspects and writing itself, this paper considers the intentions of the pajador to produce the narrative in the form of verses that express the characteristics of his regional culture. It also takes into account that Ernesto was an Italian immigrants son, and despite speaking the language in his daily life, he was literate in Portuguese and appropriated the verses of the gaucho soldier, which seems to demonstrate the fluidity of identities among the soldiers. With this study, we intend to extend the interpretations about the Lieutenants Revolt from the analysis of pajadas , which are the eyes of a soldier on the fighting. The personal documents to which we had access are analyzed by relating them to other sources, such asthe memories of the rebel Lieutenant João Cabanas. Regarding the theoretical and methodological perspectives, it is highlighted the dialogue of the recent cultural history with the micro-historical methodology, as well the discussions about the concepts of memory and representation. The historiography about the Lieutenants Revolt helps in understanding the critical of the pajador soldier who, despite being legalistic, question the military hierarchy and the conditions in which the soldiers lived. Ernesto, in turn, may have been interested in pajadas because of the taste for reading and, as a soldier, possibly identified himself with critics to the military hierarchy